2019
DOI: 10.1016/j.nbd.2018.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of matrix metalloproteinase 9 (MMP-9) protects motor neurons from TDP-43-triggered death in rNLS8 mice

Abstract: Therapeutic strategies are needed for the treatment of amyotrophic lateral sclerosis (ALS). One potential target is matrix metalloproteinase-9 (MMP-9), which is expressed only by fast motor neurons (MNs) that are selectively vulnerable to various ALS-relevant triggers. Previous studies have shown that reduction of MMP-9 function delayed motor dysfunction in a mouse model of familial ALS. However, given that the majority of ALS cases are sporadic, we propose preclinical testing in a mouse model which may be mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…Delivery of MMP-9 into FF-MNs, but not in oculomotor neurons, accelerates denervation in SOD1 G93A mice (Kaplan et al, 2014). Similarly, another study demonstrated that reduction of MMP-9 expression attenuated neuromuscular defects in rNLS8 mice expressing cytoplasmic hTDP43 ΔNLS in neurons (Spiller et al, 2019). Edaravone, a free radical scavenger which inhibits MMP-9 expression, was recently approved for the treatment of ALS in Japan, South Korea, United States and Canada (Yoshino and Kimura, 2006; Ito et al, 2008; Yagi et al, 2009).…”
Section: Intrinsic Factors Specific To Mn Subpopulationsmentioning
confidence: 93%
“…Delivery of MMP-9 into FF-MNs, but not in oculomotor neurons, accelerates denervation in SOD1 G93A mice (Kaplan et al, 2014). Similarly, another study demonstrated that reduction of MMP-9 expression attenuated neuromuscular defects in rNLS8 mice expressing cytoplasmic hTDP43 ΔNLS in neurons (Spiller et al, 2019). Edaravone, a free radical scavenger which inhibits MMP-9 expression, was recently approved for the treatment of ALS in Japan, South Korea, United States and Canada (Yoshino and Kimura, 2006; Ito et al, 2008; Yagi et al, 2009).…”
Section: Intrinsic Factors Specific To Mn Subpopulationsmentioning
confidence: 93%
“…Although the neuronal transduction of rAAV2-retro was more extensive than that of the other tested rAAVs, its efficiency needs to be further determined. As a retrograde transduction efficiency indicator, cholera toxin subunit B (CTB), is a widely used as a retrograde tracer to efficiently label lower motor neurons that correspond to specific muscles following intramuscular injection 11 , 24 , 25 . To comprehensively profile the transduction efficiency of rAAV2-retro in the spinal cord, mice were injected with a mixture of rAAV2-retro-GFP and the retrograde tracer CTB-647 at a single site of the extensor carpi radialis in the right forelimb.…”
Section: Resultsmentioning
confidence: 99%
“…MMPs are crucial in the development of CNS and many physiological processes of the adult brain by degrading ECM, but the overactivation of MMPs associated with inflammatory response was discovered in multiple neurologic disorders ( Singh et al, 2015 ; De Stefano and Herrero, 2017 ). As the most studied member, MMP9 was involved in the muscle degeneration process by enhancing ER stress, and its reduction rescued TDP-43 triggered death of motor neurons ( Kaplan et al, 2014 ; Spiller et al, 2019 ). The upregulation of MMP9 resulted in the destruction of neurovascular unit in the presymptomatic period in ALS-G93A mice, even prior to the degeneration of motor neurons ( Miyazaki et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%